2005
DOI: 10.1128/jcm.43.2.962-965.2005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Severe Acute Respiratory Syndrome Coronavirus RNA in Plasma during the Course of Infection

Abstract: We examined severe acute respiratory syndrome-associated coronavirus (SARS-CoV) RNA in plasma of 32 patients (probable SARS cases) by a quantitative real-time reverse transcription-PCR assay and reported that the highest detection rate, 75%, was found between day 5 and day 7 of illness, followed by rates of 64, 50, and 38% found between day 8 and day 11, day 2 and day 4, and day 12 and day 16, respectively. Analysis of sequential SARS-CoV load in plasma from six cases revealed different patterns of viremia, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 13 publications
1
37
1
Order By: Relevance
“…Viremia has also been implicated in the spread of many viral infections from the upper to the lower respiratory tract (9)(10)(11). Considering the possibility that this mechanism may occur in RV infections as well, of four methods used to detect the virus in this study, only the most sensitive semi-nested reverse transcription-PCR was able to detect RV in the blood.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Viremia has also been implicated in the spread of many viral infections from the upper to the lower respiratory tract (9)(10)(11). Considering the possibility that this mechanism may occur in RV infections as well, of four methods used to detect the virus in this study, only the most sensitive semi-nested reverse transcription-PCR was able to detect RV in the blood.…”
Section: Discussionmentioning
confidence: 86%
“…The mechanisms by which RV may reach the lower respiratory tract are not clear, although they may include direct inhalation of infected droplets or spread of the virus from the upper airway (6,7). Viremia has been implicated in the spread of other viral infections (8)(9)(10)(11); however, it has been considered that viremia does not occur during acute RV infection in normal individuals. Rhinoviremia has been described in case reports in five instances: in two cases of sudden, unexpected infant death (12); in two older children dying of acute respiratory disease (13,14); and in one with concomitant adenovirus disease (15).…”
mentioning
confidence: 99%
“…In isothermal conditions, RCA is capable of a 10 9 -fold signal amplification of each circle within 90 min. An efficient assay for the detection of SARS-CoV by RCA was set up in both liquid and solid phases [37], and presented preliminary results on a small number of clinical respiratory specimens. The main advantage of RCA is that it can be performed under isothermal conditions with minimal reagents and avoids the generation of false-positive results, which is frequently encountered in PCR-based assays.…”
Section: Rolling Circle Amplification-based Methodsmentioning
confidence: 99%
“…In 14 patients, RSV RNA was detected only once (n = 11) or twice (n = 3) during the course of antiviral therapy. One patient had 5 positive samples while on therapy (6,9,13,16, and 20 days after starting ribavirin; Figure 1).…”
Section: Characteristics Of Patients and Samplesmentioning
confidence: 99%
“…Although it is clear that presence of viral nucleic acid in blood is relevant for viruses such as cytomegalovirus and adenovirus, its role is less clear for respiratory viruses. Several studies have described the presence of viral nucleic acid in serum, whole blood, and peripheral blood monocytic cells of patients infected with respiratory viruses including severe acute respiratory syndrome coronavirus, influenza virus, avian H5N1 influenza virus, rhinovirus, and RSV, and have suggested a correlation with disease severity and poor outcomes [16][17][18][19][20][21][22][23][24][25]. Recently, evaluation of serum influenza RNA in HCT recipients found that influenza RNA detection was associated with hypoxemia, respiratory failure, and increased overall and influenza-related death [26].…”
mentioning
confidence: 99%